AN INNOVATIVE MASTER OF SCIENCE PROGRAM FOR THE DEVELOPMENT OF CULTURALLY COMPETENT NURSING LEADERS. - COMER, LINDA; WHICHELLO, RAMONA; NEUBRANDER, JUDY (Journal of Cultural Diversity)
The increasingly diverse population of the United States poses many challenges to the provision of health care services. Academic health care centers, community health clinics, and private providers all struggle to make services accessible and acceptable to people of many cultures, and who speak many languages. A level of cultural competence is required and organizations are having a difficult time incorporating knowledge, attitude and value changes. Studies continue to document differences in the quality of care that racial and ethnic groups are receiving. Nursing leaders are in a critical position to influence environments to optimize cultural and linguistic services. This document discusses the effectiveness of a cultural competence focus in a new master program in nurse administration. Hopefully, other educational programs will utilize lessons learned for nurse administrators.